Pengaruh Pelaksanaan Program Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan - Renita Hadiyanti; Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2017)
Human resources is a living asset owned by an organization that has an important role for the success of an organization. The success of human resource management as one of the benchmarks is in terms of employee productivity. The needs of employees in carrying out their work in order to achieve optimal work productivity need to be protected with a safe working environment, comfortable and serene, because it will cause the desire to work well. This research was conducted with the aim to know how the implementation of occupational safety and health program, how the productivity of employees work, and how much influence the implementation of occupational safety and health program on employees work productivity at PT Papyrus Sakti Paper Mill. The data collection tool in this research is by distributing questionnaires to 125 employees of production department. Analytical techniques used in the form of descriptive analysis techniques with quantitative approach. The result of descriptive statistical analysis for both variables shows the safety and health variables with employee productivity are in good category. Based on the results of testing on the implementation of occupational safety and health have a positive and significant effect on work productivity of employees. It can be proven from the calculation t count = 6.359> t table = 1.979 with the percentage of influence of 24.7%.